PENGUKURAN KESALAHAN GERAK SUMBU X DAN SUMBU Z BERDASARKAN HASIL CUTTING TEST MESIN BUBUT CNC INOVASI MENGGUNAKAN COORDINATE MEASURING MACHINE (CMM) - Helmizar, Helmizar; Agustian, Alvin Bayu; Alqap, A Sofwan F (UNIB Press, 2021)
The innovation CNC lathe is one of the machine tools with two axis. The X and Y axis are very influential in producing precision products the axis on the lathe because the axis on the lathe is as a tool for driving the chisel. To determine the precision or not of the motion of the axis, it is necessary to do a cutting test (Cutting Test) then the results of the cutting test are measured for precision using a Coordinate Measuring Machine (CMM). In the cutting test, the ISO 13041-6-M4 Series is used. In this cutting test, a radius of 50 mm is used, the test object can be reused, but the programmed radius should not be more than ± 10% of the nominal radius. The circle deviation tolerance is 0.025 mm. From the measurements made, the largest error value is 1.825056 mm in the first measurement in the CW direction, while the smallest error value is 1.824025 mm in the three-way CCW measurement, the resulting deviation continues to increase along with the cutting direction. The magnitude of the deviation, and the motion between the X-axis and the Z-axis are not collaborating with each other and not constant. This is because from the starting point of the cut on the X axis to the Z axis the deviation is getting bigger. resulting in inaccurate results from the cutting test. From the cutting test and measurements made, it can be concluded that it is necessary to make improvements to the Z axis motion.